Oral Ketamine as a Treatment for Hyper‐Responsiveness and Anxiety in a Female Allen's Swamp Monkey (Allenopithecus nigroviridis) - Juliette Nye; Elena Less; Patricia M. Dennis (Veterinary Medicine and Science)
ABSTRACT A 7‐year‐old female Allen's swamp monkey (Allenopithecus nigroviridis) was evaluated for treatment following a sequence of stressful introduction encounters with a male swamp monkey. This report describes the management of presumed stress disorder in an Allen's swamp monkey using oral ketamine.